THE INTELLIGENT CANVAS: INTEGRATING AI ACROSS THE HR, MARKETING, LEGAL, AND FINANCIAL PILLARS OF MODERN VISUAL ARTS ORGANIZATIONS - V, Kiruthiga; S, Umamaheswari; R, Joyce; Geetha, A.; T S, Rudhra; Christy, Veena (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The fast development of artificial intelligence (AI) is shifting the environment in which the visual arts organizations are organized and operate, as more and more of them implement the digital technologies in order to become more creative, efficient, and appealing to their audience. Nevertheless, even with the increased topicality of AI, its implementation in the arts industry is still sporadic and mostly limited to separate functional areas. This paper fills this gap by introducing the Intelligent Canvas framework, a three-dimensional conceptual framework integrating AI into four main pillars of an organization, namely human resource management, marketing, legal governance, and financial management. Based on the established theoretical lenses, such as the Resource-Based View, the Dynamic Capabilities Theory and the models of technology adoption, the paper builds a comprehensive picture of how AI can be used as an enabling and integrative process. The framework also focuses on the use of AI to improve talent management, customized marketing, the protection of intellectual property as well as in making financial decisions alongside the significance of cross-functional integration and ethical considerations. The paper adds to the literature by applying AI studies to the under-researched domain of visual arts organizations and providing a multi-dimensional solution to the digital revolution. The suggested model offers important implications to the researchers and practitioners who would like to use AI to achieve sustainable expansion, innovation and organizational results in the creative industry.